1999
DOI: 10.4278/0890-1171-13.3.163
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Breast Cancer Coverage in Selected Women's Magazines, 1987–1995

Abstract: The proportion of breast cancer articles to all cancer articles in these magazines (34.9%) was similar to breast cancer incidence (32.2%) but was higher than its contribution to either female cancer mortality (17.2%) or overall female mortality (4.0%). Magazines that targeted the African-American audience had fewer breast cancer articles than the other four magazines. Risk factors for breast cancer were not discussed in proportion to their impact on risk. The popular lifetime risk statistic was not explained i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(21 citation statements)
references
References 35 publications
1
18
0
1
Order By: Relevance
“…There were 340 adult PWCs in the sample, of whom 69 percent were female, with a particularly high incidence of stories involving breast cancer (73 percent of female PWCs, with the addition of five men with breast cancer), a phenomenon which has a number of causes and has been found in other media studies of cancer (Bratic and Greenberg, 1979;Gerlach et al, 1997;Marino and Gerlach, 1999;Sarna, 1995;Saywell et al, 2000). October had been designated 'Breast Cancer Awareness Week' by various influential cancer organizations, meaning that there was increased coverage of charity fundraising events and book launches relating to breast cancer autobiographies (13 PWCs were reported as having written books about their cancer experience; 11 of these were women writing about their breast cancer).…”
Section: Methodsmentioning
confidence: 93%
“…There were 340 adult PWCs in the sample, of whom 69 percent were female, with a particularly high incidence of stories involving breast cancer (73 percent of female PWCs, with the addition of five men with breast cancer), a phenomenon which has a number of causes and has been found in other media studies of cancer (Bratic and Greenberg, 1979;Gerlach et al, 1997;Marino and Gerlach, 1999;Sarna, 1995;Saywell et al, 2000). October had been designated 'Breast Cancer Awareness Week' by various influential cancer organizations, meaning that there was increased coverage of charity fundraising events and book launches relating to breast cancer autobiographies (13 PWCs were reported as having written books about their cancer experience; 11 of these were women writing about their breast cancer).…”
Section: Methodsmentioning
confidence: 93%
“…Research has also found that the images which support these themes converge on that of a young, professional white woman who tells a story of developing breast cancer and overcoming the adversity she faces (Anglin, 1997;Cartwright, 1998;Lantz & Booth, 1998;Marino & Gerlach, 1999;Wong & King, 2008). Cartwright's analysis of visual media similarly notes how breast cancer activism is constructed around a set of signifiers that describe the woman with breast cancer as white, straight, middle to upper class, urban, educated and professional.…”
Section: The Marketing Of Breast Cancer Messagesmentioning
confidence: 89%
“…Content analyses of magazine articles have found that proportionately few articles depict African American women, or discuss their likelihood of developing breast cancer (Andsager et al, 2000;Andsager & Powers, 1999, 2001Frisby 2002;Marino & Gerlach, 1999). For example, a comparison of popular women's magazines found few articles about breast cancer among those magazines targeted to African Americans (Marino & Gerlach, 1999).…”
Section: The Marketing Of Breast Cancer Messagesmentioning
confidence: 94%
See 1 more Smart Citation
“…First, most studies of cancer in the media where a comparative count is done find that breast cancer is over-reported compared to its incidence in the population , Dymock and Hill 1999, Gerlach et al 1997, Marino and Gerlach 1999, Sarna 1995, Saywell et al 2000 as it appeals to news editors for a variety of (largely sexist) reasons (Henderson and Kitzinger 1999, Lantz and Booth 1998, Lupton 1994. For this study, though, a further reason is that the first week of October has been designated`Breast Cancer Awareness Week' by various influential cancer organisations, meaning that there was increased coverage of charity fundraising events and book launches relating to breast cancer autobiographies (13 PWCs were reported as having written books about their cancer experience; 11 of these were women writing about their breast cancer).…”
Section: Methods and Samplementioning
confidence: 99%